(untitled) - Black, Rob (Hoboken, N.J., 2005)
It provides a blueprint of what you need to do to ensure a well-funded life and covers topics such as: common money management mistakes and how to avoid them, how to get and stay out of debt, new ways to work, investing in real estater, financial planning essentials for couples, how to raise money-savvy kids, the best ways to save for college, retirement
Keywords: Finance, personal